Intramolecular Annulation of Gossypol by Laccase to Produce Safe Cottonseed Protein - Wang, Lin; Chen, Ming; Luo, Xuecai; Fan, Yanan; Zheng, Zai; He, Zongqin; Yin, Ruochun; Meng, Tao; Xu, Shuyang; Pan, Yu; Su, Jihu; Du, Jiangfeng; et al. (Frontiers in Chemistry, 2020)
The presence of the phenol gossypol has severely limited the utilization of cottonseed meal and oil in the food and animal feed industries. Highly efficient means of biodegradation of gossypol and an understanding of the cytotoxicity of its degradation products remain outside current knowledge and are of universal interest. In this work, we showed for the first time that laccase can catalyze the intramolecular annulation of the aldehyde and hydroxyl groups of gossypol for the o-semiquinone radical and originate the released ·OH radical. It was further found that the oxidation of aldehyde groups significantly decreases reproductive toxicity and hepatotoxicity. These results indicate a novel detoxification pathway for gossypol and reveal the crucial role played by radical species in cyclization. This discovery could facilitate the development of safe, convenient, and low-cost industrial methods for the detoxification of cotton protein and oil resources.